Supplementary Material For Publication "Pore-Scale Salinity Effects On Methane Hydrate Dissociation" By Almenningen Et Al - Almenningen, S.; Iden, E.; Fernø, M.A.; Ersland, G. (Zenodo, 2018)
Supplementary materials for publication "Pore-scale salinity effects on methane hydrate dissociation" Abstract: Sedimentary methane gas hydrates may become a significant source of methane gas in the global energy mix for the next decades. The widespread distribution of methane hydrates, primarily in subsea sediments on continental margins, makes the crystalline compound attractive for countries with shorelines that seek self-sustainable energy. Fundamental understanding of pore-level methane hydrate distribution and dissociation pattern is important to anticipate the gas production from hydrate reservoirs. Especially the effect of local salinity gradients on dissociation characteristics must be understood as the aqueous phase in most reservoirs is saline. We evaluate the pore-level salinity effect on hydrate dissociation experimentally using silicon-wafer micro-models capable of withstanding high internal pressures. Methane hydrates were formed with brines for a range of salinities (0.0, 2.0, 3.5 and 5.0 wt% NaCl), and we study hydrate dissociation during both depressurization and thermal stimulation, which currently are the most cost-effective production methods. The laboratory results show how initial pore-scale hydrate distribution prior to dissociation affect the melting and mobilization of gas. The local pore-water salinities influenced the stability of the hydrate structure, and led to distinct dissociation patterns due to water freshening.